India’s Afghan Journey: Where from here? - Attar Rabbani (Journal of Political Studies, 2013)
India’s contemporary Afghan journey is a tale of tailored interest with qualified destiny of Afghanistan. India embarked on afghan journey more aggressively only after the fall of ruling Taliban in 2001 with defined geo-political objectives, firmly placed under the security cover of NATO occupation of the country. The objectives of NATO and New Delhi not only squarely merged in Kabul but also found identical companion – Northern Alliance – to realize stable Afghanistan. The most aggressive presence of New Delhi in Afghanistan was its political, economic and diplomatic investment with choreographed goals, revolving around the critical desire of favored strategic response from government in Kabul and NATO. With planned withdrawal of NATO forces, New Delhi however faces decisive challenge for its ongoing operation in the country. The diminishing security cover of NATO and growing influence of Taliban would eventually paralyze New Delhi’s maneuvers. Given these uncomforting realities, where and how New Delhi shall go from here? What is the nature of Indian interest and its significance in that country? More significantly what Islamabad would make of this? This paper explores India’s surging challenge in Afghanistan and argues that it would have to be much more attentive to regional callings, chiefly emanating from Pakistan, and China and carefully prefer its pathways ahead. India’s prospective preferable pathways notwithstanding, South Asia shall continue to be a problematic region from ‘stability’ and ‘peace’ perspectives.